ANALISIS FAKTOR INTERN DAN EKSTERN YANG MEMPENGARUHI KESULITAN BELAJAR SISWA PADA MATA DIKLAT KETERAMPILAN KOMPUTER DAN PENGELOLAAN INFORMASI DI SMK - triyaningsih, ninik (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
The purposes of this research are, (1) To determine the internal and external factors which influence students learning difficulty in computer skills and management information courses at the tenth (X) grade students of administrative offices class, SMK Negeri 1 Surakarta in the 2011/2012 school period (2) To determine the most dominant factors both internal and external which influence students learning difficulty in computer skills and management information courses at the tenth (X) grade students of administrative offices class, SMK Negeri 1 Surakarta in the 2011/2012 school period (3) To know the efforts used in overcoming the students learning difficulty and progressive actions in order to make the courses run effectively.The result of this research are (1) Internal factors that affect students' learning difficulty can be seen from the physiological and psychological factors. Physiological factors that student health is not always healthy and the disabled body minus the eye disorder, whereas psychological factors, namely the level of student intelligence, talents, interests, motivation, mental health, and particular types of learning. Furthermore, external factors that affect students' learning difficulty can be seen from the factor of family, school, mass media and social environment. Family factor are parental controls for children's learning is low, the atmosphere tends to crowded houses, and family economic situation is lacking. Factors that school facilities provided by the school especially the computers were damaged, and the time that school discipline is still low. Factor of social media and the intensity of students' access to the mass media too often and less supportive social environment. (2) Internal factors are the most dominant in influencing students' learning difficulties is the talent where supported the student's skills. The most dominant external factors influencing student learning difficulties is the mass media, when the student's learning time is use for enjoying media. (3) The work done to overcome the learning difficulties of students and the progressive step to streamline the learning includes the pre, process, and post. Preparation of the pre-form of learning in which teachers prepare the syllabus and Learning Implementation Plan. Stage of the process in the form of providing guidance that does not cause confusion of students, encouraging students to participate actively in the class, motivating students, and focus on the learning process. Stage in the form of a post is make a remedial for students who got difficulties in the learning process. Key words: internal factor, external factor, learning disabilities